PENGUJIAN CUTTER ENDMILL HSS DIAMETER 12 MM DENGAN PEMOTONGAN DEPT OF CUT TERHADAP BAJA AMUTIT DI MESIN MILLING LAGUN FU 100 (LFR 25) - Adi S., Antonius Adi S Thopo; Diratama, Mohamad Yazid; Daniswara, Wandi (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2024)
This study aims to analyze the relationship between machining parameters and tool wear (flank wear) in the milling process of amutite steel (SKS3) using a 12 mm diameter High-Speed Steel (HSS) endmill cutter. The machining parameters studied included cutting speed (Vc = 14 m/min and 18 m/min), feed rate (F = 30 mm/min and 75 mm/min), and depth of cut (Doc = 0.5, 1, 1.5, 2 and 2.5 mm). The linear regression method was used to build a mathematical model relating these parameters to tool wear. Experimental data were obtained through a series of machining tests with predetermined parameter variations. The regression analysis results showed that tool wear or flank wear (Vb) was significantly affected by cutting speed (Vc), feed rate (F), and depth of cut (Doc), with constant and exponent values obtained through logarithmic transformation and regression analysis. The regression model obtained has a good level of accuracy in predicting tool wear, although there is a difference between the theoretical and actual Vb values. This discrepancy may be caused by factors not measured in the experiment, such as variations in workpiece material or environmental conditions. This research also provides that the 12 mm diameter HSS endmill cutter is proven to be capable of carrying out the depth-of-cutting process on amutite steel material in the Lagun FU 100 milling machine with the specified depth-of-cut.